Soybean Supply Response Model In Sub-Optimal Land In Tanjab Timur District: Application Of The Meta Response Function - Edison, Edison (International Journal of Science, Technology & Management, 2023)
Soybean production in the Tanjab Timur region has been on a downward trend for nearly a decade. This requires attention and assessment to find solutions to existing problems. The objective of study is to (1)evaluate the use of inputs and their effect on production, as well as investigate the capacity of production factors, such as landand other factors to analyze supply responses; and (2) analyze soybeansupply response variable to the components of input costs, gross revenue, and other variables, to produce a soybean supply response model in sub-optimal land types: Application of Meta-Response Functions. This research was conducted in 2021 on peatland types (sub-optimal). Stratified random sampling is used for the land area.Appropriate qualitative and quantitative data analysis methods are used, called the Meta Response Function, which in their application is distinguished from the research objectives, namely in the first objective using the Production Function Empirical Model, and in the second using the Meta-Response Model. The results showed that soybean farmers on peatland in the research area respond to changes in input use efficiently. In terms of output supply, it responds to soybean production. In terms of input demand, many variables aresensitive to the use of labor, maintenance, and harvesting labor. Production elasticity completes the policy section of the database foranalysis of the policy impact of applying alternative inputs on soybeansupply and input demand.